Treatment of avulsion fractures of the intercondylar eminence by medial parapatellar approach, open reduction and cross wire fixation. Issue 4 (July 2015) - Keshet, Doron; Zaidman, Michael; Eidelman, Mark
Abstract : Avulsion fractures of the intercondylar eminence in children and adolescents are relatively uncommon and can lead to significant disability with improper union. Many operative techniques have been developed to fixate these fractures, most of them utilizing sophisticated fixation modes. In this study, a small medial parapatellar approach was used with open reduction and percutaneous cross Kirschner wire fixation. The aim of this study was to evaluate the effectiveness of this method. From 2007 to 2012, eight children were treated, mean age 11.8 years (range 10–14 years). All underwent open reduction by a medial parapatellar incision and fixation by two cross Kirschner wires introduced in an oblique crossed manner from the medial and lateral aspects of the proximal tibia. Fractures were classified as Meyers and McKeever type III and were not candidates for conservative treatment. All operated limbs were immobilized postoperatively in a circular cast in extension for 6 weeks and allowed partial weight bearing from day 1 after the procedure. Outcomes were evaluated clinically and through radiographs taken during follow-up. All fractures were successfully reduced and healed, with no occurrences of malunion or nonunion. At follow-up, all patients had full knee range of motion, there was no gross laxity of the knee compared with the contralateral knee, and good functional outcome was achieved. On the basis of our experience, we believe that the procedure that we used is a simple, low-tech, and minimally invasive technique for the treatment of these fractures, with good functional outcome.